Essays on the economics of education - Goldemberg, Diana (2019)
Education is a powerful tool to improve lives and enhance the development prospects of nations. While primary and secondary school enrollment have increased considerably over the past decades in Brazil, completion rates and learning have remained low. This dissertation consists of three empirical essays, the first two focused on factors that may be holding back completion rates and the last one tackling the unsatisfactory learning levels. The first essay analyses the impact of cumulative heat exposure on educational outcomes in the Brazilian Northeast. Using data from over 78 thousand schools, I find that a one-degree Celsius increase in the annual mean maximum temperature during the school year reduces grade progression by 0.35 percentage points and increases dropout rates by 0.26 percentage points. Results are consistent with established links between temperature and cognitive performance and have important implications for evaluating the welfare-burden of climate change. The second essay, written jointly with Emily Hanno, examines the consequences of chronic exposure to community violence for children’s academic progression in Rio de Janeiro, relying on longitudinal data for five cohorts of children attending municipal schools in the city. We estimate that a single year of exposure to high violence during the first four years of elementary school leads to a 6.9 percentage points reduction in the probability of reaching fifth grade on time, with effects being more than twice as large for children facing four years of high violence. The third essay evaluates a peer mentoring program for school principals implemented in Ceará in 2008. Exploiting a regression discontinuity design for the school rank defining program participation, I find that low performing schools participating in the program subsequently achieve education quality indexes that are 0.18 standard deviations higher. Similarity in number of enrolled students and proximity between paired schools are associated with stronger outcomes for low performing participants, indicating that matching of mentee-mentors deserves careful consideration. These findings provide an example of how school turnaround may be achieved systemically without leadership replacement.